2020
DOI: 10.1002/gps.5452
|View full text |Cite
|
Sign up to set email alerts
|

Reframing dementia: Nursing students' relational learning with rather than about people with dementia. A constructivist grounded theory study

Abstract: Objectives Developing an informed and effective workforce that provides effective and ethical care to people with dementia and their families is an international priority. Here we explore the impact of a novel approach on students of adult nursing. It involved engagement with people with dementia and their carers over 3 years in the Time for Dementia Programme. This research explored students' perceptions of their professional learning and practice. Methods A longitudinal, constructivist grounded theory approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…As in our earlier study of medical students, 9 TFD did not appear to change quantitative measures of empathy, unlike our two qualitative studies 10,21 which identified positive change in terms of empathy towards people with dementia. In terms of potential explanations, first JSE is a generic empathy measure, and its potential limitation in measuring empathy towards people with dementia has been identified in a wider systematic review of empathy interventions for people with dementia.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…As in our earlier study of medical students, 9 TFD did not appear to change quantitative measures of empathy, unlike our two qualitative studies 10,21 which identified positive change in terms of empathy towards people with dementia. In terms of potential explanations, first JSE is a generic empathy measure, and its potential limitation in measuring empathy towards people with dementia has been identified in a wider systematic review of empathy interventions for people with dementia.…”
Section: Discussioncontrasting
confidence: 57%
“…The students are in effect taught by the people with dementia and their families, and it enables them to see the world and healthcare through their eyes. 21 This identification with the person with dementia and their carer and relational learning which takes place appears to be powerful in terms of knowledge and attitude change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it still focuses on treating specific symptoms (e.g., challenging behavior) [ 7 ], as well as diagnostic [ 8 ] and end-of-life care [ 9 , 10 ]. Programs are characterized by inconsistencies and gaps in professional dementia education [ 11 ]. Evidence shows that there are deficits in knowledge of dementia and inadequate skills in key elements of dementia care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…challenging behavior) (7) as well as on diagnostic (8) and providing end-of-life care (9,10). Programs are characterized by inconsistency and gaps in professional dementia education (11). Therefore, evidence suggests de cits in knowledge of dementia and inadequate skills in key elements in dementia care.…”
Section: Introductionmentioning
confidence: 99%